2D amorphous-MoO3−x@Ti3C2-MXene non-van der Waals heterostructures as anode materials for lithium-ion batteries. (August 2021) - Yan, Pengfei; Ji, Liang; Liu, Xiaopeng; Guan, Qinghua; Guo, Junling; Shen, Yonglong; Zhang, Haijun; Wei, Weifeng; Cui, Xinwei; Xu, Qun
Abstract: 2D heterostructures offer a great opportunity in seeking high-performing energy storage materials; however, performance ceiling exists, limited by their van-der-Waals (vdW) interactions. Here, we explore a novel 2D, amorphous MoO3−x (aMoO3−x ) on Ti3 C2 -MXene, non-vdW heterostructure via a facile synthesis route. Density functional theory computations suggest that the non-vdW heterostructure can strongly stabilize aMoO3−x while maintaining electrical conductivity at a high level. Facile 2D Li-ion diffusion can then be achieved in the restacked 2D non-vdW heterostructures due to the weakened interactions between two defective MoO3−x layers, leading to a capacitor-like interlayer diffusion reaching a large capacity of 426 C g −1 on the surface of the amorphous layer and a diffusion-controlled intralayer diffusion of 546 C g −1 within the amorphous layer. These characteristics optimize Li-ion storage kinetics while achieving full capacities of amorphous materials with high stability. This work might offer a feasible platform of 2D non-vdW heterostructures for boosting and understanding Li-ion storage performance. Graphical Abstract: 2D aMoO3−x @MXene non-vdW heterostructures have been fabricated via a facile synthesis route using in-situ formed HCl to etch Al. The non-vdW heterostructures stabilize aMoO3−x strongly while maintaining conductivity and Li-ion diffusion at a high level, promoting the synergistic properties of a high capacity, excellent rate capability, and improved cyclability. ga1 Highlights: A novel and facile strategy was presented to synthesize non-vdW heterostructures. The unique non-vdW heterostructure leads to excellent electrochemical properties. Synergistic effects of the heterostructures were understood from an atomic scale. A large capacitor-like interlayer diffusion (426 C g −1 ) contributes to high kinetics.